2019
DOI: 10.1590/1517-869220192506220279
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Muscle Function in Prostate Cancer Survivors Receiving Different Treatment Regimens

Abstract: Introduction: Prostate cancer is the most prevalent neoplastic disease in men. After diagnosis, different treatment regimens are proposed based on the stage of the cancer. These treatments affect physical and muscle function, quality of life, and prognosis differently. Objectives: To assess fatigue, muscle strength, muscle thickness, and muscle quality in prostate cancer survivors undergoing androgen deprivation therapy (ADT). Methods: Ten ADT patients, eight non-ADT patients and 18 healthy control subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Specifically, for men, among the components of metabolic syndrome, waist circumference, triglycerides, HDL cholesterol, and fasting blood glucose showed an important relationship with relative handgrip strength. According to a previous study, 38 prostate cancer survivors receiving androgen deprivation therapy showed lower muscle strength and function that could lead to metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for men, among the components of metabolic syndrome, waist circumference, triglycerides, HDL cholesterol, and fasting blood glucose showed an important relationship with relative handgrip strength. According to a previous study, 38 prostate cancer survivors receiving androgen deprivation therapy showed lower muscle strength and function that could lead to metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que os diversos tratamentos do CP podem afetar de forma diferente a capacidade física dos sobreviventes. A terapia de privação androgênica, por exemplo, pode potencializar a perda de força muscular, de capacidade de trabalho e de tecido muscular esquelético, além de aumentar a percepção de fadiga física, em função da inibição da produção de testosterona (12). Entretanto, faz-se necessário saber se os tratamentos do CP também promovem diferentes efeitos na funcionalidade dos pacientes, modificando as atividades da vida diária.…”
Section: Palavrasunclassified
“…Estudos demonstraram que homens submetidos a TPA, principalmente em exposições mais prolongadas, apresentam um maior aumento na massa gorda e uma menor quantidade de tecido muscular esquelético, quando comparados com homens com CP submetidos a outros tipos de tratamento e a homens saudáveis (12,16). Estudos longitudinais demonstram que homens em tratamento com TPA com duração entre 36 -52 semanas apresentaram ganho de gordura substancial, entre 9,4% e 19,3%, e diminuição na massa magra (17).…”
Section: Fundamentação Teóricaunclassified
“…The amount of familiarization sessions required to avoid learning effect and to improve reliability of measurements in isokinetic testing seems to vary according to the population tested. Several studies have used isokinetic tests to assess muscle function of cancer survivors [10,12,35]. However, to our knowledge, no studies to date have assessed the amount of familiarization sessions required by breast cancer survivors to produce a reliable and accurate measurement using isokinetic dynamometry testing.…”
Section: Introductionmentioning
confidence: 99%